Avaliação do equilíbrio e do nível de independência funcional de idosos da comunidade - Ferraresi, Juliana Rizzatto; Prata, Melina Galetti; Scheicher, Marcos Eduardo (Universidade do Estado do Rio Janeiro, 2015)
Objectives:To compare the balance and level of independence of elderly persons and to correlate these variables with age, cognitive status and number of medications taken.Methods: A total of 172 individuals, aged over 60 and without cognitive deficit were included in the study. The risk of falls was performed using the Berg Balance Scale and functional independence through the Barthel Index. Correlations were performed by Spearman's correlation index, and association was tested with the chi-square test, with p≤0.05 considered significant.Results:There was a moderate correlation between the risk of falls and functional independence (r=0.38; p<0.0001). There was also a statistically significant correlation between age and risk of falls (r=-0.43; p<0.0001). With regard to the association between the risk of falls and drugs, it was observed that elderly people who took three or more medications fell twice as often (p<0.0001).Conclusion:The results found a correlation between the risk of falls and functional independence, and also that older elderly persons, and those who took a greater number of medications, were more at risk of falls.

Objetivos:Comparar o equilíbrio e o nível de independência de idosos da comunidade e correlacionar essas variáveis com idade, estado cognitivo e número de medicamentosMetodologia: Participaram da pesquisa 172 idosos da comunidade, com 60 anos de idade ou mais sem déficit de cognição. A avaliação do risco de quedas foi feita por meio da Escala de Equilíbrio de Berg e a independência funcional, por meio do Índice de Barthel. As correlações foram feitas pelo Índice de Correlação de Spearman e a associação, pelo teste de Qui-quadrado, sendo aceito um valor de p≤0,05 como significante.Resultados: Houve uma correlação moderada entre o risco de queda e a independência funcional (r=0,38; p<0,0001). Também houve resultado estatisticamente significante entre a idade e o risco de queda (r=-0,43; p<0,0001). Na associação entre o risco de queda e medicamentos, percebeu-se que idosos que ingeriam três ou mais medicamentos apresentaram um risco duas vezes maior de cair com p<0,0001.Conclusão: Os resultados indicaram haver correlação entre o risco de queda e a independência funcional; além disso, observou-se que uma idade avançada está ligada a um maior risco de queda e uma maior quantidade de medicamentos ingeridos também leva a um risco elevado para quedas.
Assessment of balance and level of functional independence of elderly persons in the community
Keywords: Aging; Postural Balance; Dependency; Activities of Daily Living; Envelhecimento; Equilíbrio Postural; Dependência; Atividades Cotidianas